2013
DOI: 10.1016/j.molcel.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an RNA Silencing Complex of the CRISPR-Cas Immune System

Abstract: Summary Bacterial and archaeal CRISPR (Clustered Regularly Interspaced Short Palindromic Repeat) loci capture virus and plasmid sequences and use them to recognize and eliminate these invaders. CRISPR (cr)RNAs containing the acquired sequences are incorporated into effector complexes that destroy matching invader nucleic acids. The multi-component Cmr effector complex cleaves RNA targets complementary to the crRNAs. Here we report cryo-electron microscopy reconstruction of a functional Cmr complex bound with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
166
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(191 citation statements)
references
References 50 publications
15
166
1
1
Order By: Relevance
“…Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013). Euryarchaea are more diverse phylogenetically than crenarchaea because of they are generally heterotophic in nature and frequent a wide range of natural environments (Vestergaard et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Vestergaard et al (2014) also classified the cas subtypes based on cas-protein occurrences for archaea. Phylogenetic analysis of this study also revealed that many functions of the identified cas proteins could be derived from distantly related genomes, plasmids and phages that was agreed to earlier findings (Nelson et al 1999;Zivanovic et al 2002;Boucher et al 2003;Marraffini and Sontheimer 2009;Chellapandi and Ranjani 2011;Spilman et al 2013). Euryarchaea are more diverse phylogenetically than crenarchaea because of they are generally heterotophic in nature and frequent a wide range of natural environments (Vestergaard et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Type II CRISPR systems are characterized by Cas9, a multidomain protein with a bilobed architecture harboring two nuclease sites that together catalyze cleavage of invading DNA (12, 21-24). The Csm system in CRISPR type IIIA and a related Cmr complex in type IIIB cleave DNA and RNA, respectively, forming a helical structure around crRNA that is structurally similar to Cascade (14,17,18,25,26).Whereas Cas9 and Csm/Cmr effector complexes directly recognize and nucleolytically degrade invading genes (12, 14, 16, 17, 21), Cascade complex by itself is not a nuclease for degradation of invader DNA (13). In Escherichia coli K-12 (type IE), Cascade recognizes and binds crRNA to complimentary sequence in target DNA, generating an RNA mediated displacement loop (R-loop) of single-stranded (ss) DNA and RNA-DNA hybrid within double-stranded (ds) target DNA (13).…”
mentioning
confidence: 99%
“…In vivo, several copies of Cas7 proteins are wrapped around crRNA in a sequence-unspecific helical fashion [5,30,50,51]. Crystal structures from single and complex-bound Cas7 proteins show two composite RNA-binding surfaces: a central cleft and a structurally variable insertion domain [5,23,24,52].…”
Section: Mapping the Rna Binding Interface In Cas7 Proteinsmentioning
confidence: 99%